2006
DOI: 10.1074/jbc.m605251200
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation by Default, a Potential Mechanism for Regulation of Insulin Receptor Substrate-1/2, Akt, and ERK1/2

Abstract: Protein phosphorylation is an important mechanism that controls many cellular activities. Phosphorylation of a given protein is precisely controlled by two opposing biochemical reactions catalyzed by protein kinases and protein phosphatases. How these two opposing processes are coordinated to achieve regulation of protein phosphorylation is unresolved. We have developed a novel experimental approach to directly study protein dephosphorylation in cells. We determined the kinetics of dephosphorylation of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Primary mouse hepatocytes (C57/BJ6) were isolated by a modified noncirculating collagenase perfusion method as described (Berry & Friend 1969, Zhande et al . 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Primary mouse hepatocytes (C57/BJ6) were isolated by a modified noncirculating collagenase perfusion method as described (Berry & Friend 1969, Zhande et al . 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, our present findings suggest that chronic serine phosphorylation of IRS-1 induced by oligomeric Aβ activation of IRS-1 serine kinases may be a cause of brain insulin resistance in AD. This would dampen signal transmission at all subsequent levels of the IRS-1 signaling pathways, reducing insulin responsiveness of Akt, GSK-3, mTOR, and ERK2, although the last would be via an interaction of IRS-1 with Grb2, not PI3K (79,80,134).…”
Section: Brain Insulin Resistance At the Level Of Irs-1 And Downstreamentioning
confidence: 99%
“…Our results showed that HBV‐induced collagen type I expression was alleviated by inhibition of p38 MAPK, but not blocking of TGF‐β, indicating that p38 MAPK is the major intracellular pathway responsible in HBV‐induced collagen I expression. The p38 MAPK represents one of the central kinases that typically transduces signals generated by growth factors and stress 26 . The p38 MAPK signaling has been implicated in TGF‐β‐mediated signaling and collagen gene expression 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK represents one of the central kinases that typically transduces signals generated by growth factors and stress. 26 The p38 MAPK signaling has been implicated in TGF-b-mediated signaling and collagen gene expression. 17 TGF-b affects extracellular matrix homeostasis by inducing the metalloproteinase-13 gene, requiring expression and activation of the p38 MAPK pathway, which involves activation of Smad3 by p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%